Non-cognitivism and wishful thinking - Dorr, C (Blackwell Publishing Inc., 2002)
Even if non-cognitivists about some subject-matter can meet Geach’s challenge to explain how there can be valid implications involving sentences which express non-cognitive attitudes, they face a further problem. I argue that a non-cognitivist cannot explain how, given a valid argument whose conclusion expresses a belief and at least one of whose premises expresses a non-cognitive attitude, it could be reasonable to infer the conclusion from the premises.